What remains after transient global amnesia (TGA)? An ultra‐high field 7 T magnetic resonance imaging study of the hippocampus. (29th October 2019) - Paech, D.; Kuder, T. A.; Roßmanith, C.; Griebe, M.; Eisele, P.; Platten, M.; Ladd, M. E.; Schlemmer, H. ‐P.; Gass, A.; Szabo, K.
Abstract : Background and purpose: The aim was to study whether ultra‐high field 7 T magnetic resonance imaging (MRI) can demonstrate chronic focal defects in the hippocampus corresponding to the former acute diffusion‐weighted imaging (DWI) lesions and to assess chronic T2‐hyperintense hippocampal lesion load in transient global amnesia (TGA) patients. Methods: Follow‐up of 7 T MRI of the hippocampus was performed in 13 patients with documented hippocampal DWI lesions (detected via 3 T MRI) after acute TGA. The location of the DWI lesions was transformed to 7 T T2 images after data co‐registration. Additionally, the T2‐hyperintense lesion load was estimated in each patient and compared with that of 13 healthy controls. Results: Magnetic resonance imaging (7 T) was performed after a median of 4 months. No structural abnormality at the site of the previous TGA lesion was observed in any case. None of the controls showed DWI lesions. There was no significant difference between patients and controls concerning the number ( P = 0.67) or volume ( P = 0.45) of T2‐hyperintense hippocampal lesions. Conclusions: Diffusion‐weighted imaging lesions in patients with TGA do not provoke any visible sequelae and do not result in hippocampal cavities. The occurrence of incidental hippocampal T2 lesions after TGA is not more frequent than in controls.